IMPROVEMENT OF MODERN METHODS OF TREATMENT OF CHRONIC PERIODONTITIS - Normuradov Nodirjon Alisherovich; Muratova Saodat Kadirovna (European Science Publishing, 2024)
The article is of great theoretical and practical importance, written to improve, enhance and enlarge the knowledge of students. The article entitled ‘Improvement of modern methods of treatment of chronic periodontitis in therapeutic dentistry’ includes all the achievements and innovations of today. It forms knowledge about the concept of the origin of periodontitis, essence, characteristics and forms, methods of treatment, materials used. The relevance of the information given in the article, the planned methods of treatment using foreign literature and the results obtained after treatment have clinical and statistical basis.
Keywords: periodontium, chronic, acute, complications, inflammation, infection, tissue.